2017
DOI: 10.1245/s10434-017-5967-3
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Phase 2 Study on the Feasibility and Efficacy of Neoadjuvant Chemotherapy Without Radiotherapy for Locally Advanced Rectal Cancer

Abstract: The findings show that NAC is a feasible and promising treatment option for LARC (This study is registered with UMIN-CTR, UMIN000005654).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 30 publications
1
45
0
1
Order By: Relevance
“…R0 resection rate after NAC was 100% among patients who were judged to be capable of undergoing radical excision at baseline. Previous reports also showed the R0 resection rates of NAC for cT3-4 (except T4b) were high, ranging from 98.3% to 100% (11)(12)(13)(14). An important problem inherent in preoperative treatment is that surgical curability may be impaired by tumour growth during the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R0 resection rate after NAC was 100% among patients who were judged to be capable of undergoing radical excision at baseline. Previous reports also showed the R0 resection rates of NAC for cT3-4 (except T4b) were high, ranging from 98.3% to 100% (11)(12)(13)(14). An important problem inherent in preoperative treatment is that surgical curability may be impaired by tumour growth during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The pCR rate might increase with the addition of a molecular-target drug. The pCR rate was 13.3%-25% for regimens that involved bevacizumab (11)(12)(13)15) and was 18% for regimens that involved cetuximab (13). However, the relationship between histological response and prognosis in NAC has not been clarified, though many reports on NACRT showed pCR and good histological response were associated with a good prognosis (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…[457][458][459][460] As for locally advanced rectal cancer, abundant phase II studies have been conducted for the neoadjuvant use of anti-EGFR or anti-VEGF therapy, with pooled estimated pCR values of 27% and 14% being reported for bevacizumab-and cetuximab-relevant regimens, respectively, via a meta-analysis of 32 previous studies. 448 Although newer trials echoed the results from metaanalysis, 461 to elucidate whether the targeted agents are truly effective in the neoadjuvant setting still requires larger population-based head-to-head, time-to-event data. It is worth noting that the efficacy of immune checkpoint modulators for the neoadjuvant treatment of CRC has been investigated in various ongoing trials, offering more potential choices in the future (NCT03926338, NCT03299660, NCT03102047, NCT04130854, NCT03854799, and NCT02754856).…”
Section: Immune Checkpoint Inhibitor Therapymentioning
confidence: 99%
“…The advantages of NAC include possible improved OS by introducing intensive chemotherapy (such as FOLFOX and XELOX, including oxaliplatin) at an early stage; reduced postoperative anal dysfunction, postoperative complications, and late effects due to radiation; and a high completion rate of chemotherapy compared to postoperative adjuvant chemotherapy. A summary of reports (10,(12)(13)(14)(15)(16)(17)(18)(19) of pCR rates using NAC and NACRT is shown in Table IV. In recent reports on the effects of NAC on local control, Schrag et al (14) found a pCR rate for the primary lesion of 25% after 6 courses of FOLFOX and bevacizumab, and Kamiya et al (15) reported a pCR rate of 12.2% after 4 courses of XELOX and a rate of 31.7% for a tumor regression grade (TRG) ≥3.…”
Section: Discussionmentioning
confidence: 99%